Analisis Implementasi Keselamatan dan Kesehatan Kerja di Tambang Batubara Bawah Tanah PT. Cahaya Bumi Perdana dalam Rangka Pembentukan Sistem Manajemen Keselamatan dan Kesehatan Kerja - Andri Van Deni; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2018)
Abstract. The mining has to identify the hazards, assess the associated risks and bring the risks to tolerable level on a continuous basis. The number of work accidents in the company are tend to increase, not only that statistic data but also the effectife temperature between 27-29 oC in the tunnel, dangerous mining gases, and lack of use of personal protective equipment by workers, and lack of identification of hazards in some work environments. Based on the problem, this study aims to reveal the application of the company's OSH, statistics on workplace accidents, potential hazards in the work environment and recommend several standard operating procedures. The results of work accident statistics at PT Cahaya Bumi Perdana from 2012-2017 showed that there were fluctuations in the severity and frequency of accidents, with an average FR value is 39.6 and an SR value is 38 days lost. The hazards cannot be completely eliminated, but the hazards of the work environment can be minimized. in this research we are using JSA and JHA methods to identifying and analysing the hazards associated with an activity. JSA and JHA used to identify work hazards in ventilation, supporting systems, lori transportation, and coal replacement. After doing the hazards identification, to controlling it will be given a recommendation. Not only made a hazards identification but also to creating a Standard Operating Procedure for a few jobs. With analyze Both of that requirement, it should be making an eazy ways to forming a management system of occuptional safety and health.Keywords: Safety, Health, Hazards, Mining, Underground